PENGARUH KEPEMIMPINAN, KEDISIPLINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS MELALUI KINERJA KARYAWAN (Studi Empiris Pada Perusahaan Daerah Perkebunan (PDP) Kabupaten Jember) - Halil, Halil; K, Bagus P. Yudhia; Kustiari, Tanti (Universitas Jember, 2015)
ABSTRACT Halil1, Bagus P. Yudhia K.2, Tanti Kustiari2 1 Mahasiswa Program Studi Agribisnis Program Pascasarjana Magister Terapan Politeknik Negeri Jember. 2 Dosen Pascasarjana Magister Terapan Politeknik Negeri Jember. Alamat: Jl. Mastrip, Jawa Timur 68101, Indonesia +62 331 333352 Â There were many issues of human resources management at the Perusahaan Daerah Perkebunan (PDP) Jember. While the competition just makes it more difficult especially increase competitiveness. The purpose of this study was to determine the effect of leadership, discipline and motivation on employee performance, and determine the effect of leadership, discipline, motivation and performance of employee productivity. This study uses a confirmatory approach and PDP Jember as an object of research. Data were analyzed using path analysis. The results showed that the leadership, discipline and motivation significantly influence employee performance and leadership, discipline, motivation and employee performance significantly influence employee productivity. Â Â Keywords: Leadership, Discipline, Motivation, Performance, Productivity, PDP Kab. Jember, Path Analysis.